Assessing Health Impacts of Winter Smog in Lahore for Exposed Occupational Groups - Fatima Jabeen (MDPI AG, 2021)
The goal of this research was to investigate the health effects of winter pollution on various occupations in Lahore and its neighboring peri-urban areas. A questionnaire survey, key informants, and focused group discussions were employed to collect data, which included demographic, socioeconomic, and health-related information. Descriptive statistics and the multivariate logistic regression model (MLRM) were used to examine the effects of pollution on exposed occupational groups who experienced symptoms such as coughing, shortness of breath, and eye discomfort. According to data from interviews, MLRM revealed that individuals working in various occupations with outdoor and indoor environments are equally affected by winter smog, but being middle-aged (odds ratio OR = 5.73), having a history of a respiratory ailment (OR = 4.06), and location (OR = 2.26) all play important roles in determining health. However, less educated people, elders, and people who already live in polluted areas are more likely to develop respiratory health symptoms. During the smog incident, it was determined that diverse health and socioeconomic factors exacerbate an individual’s negative health impact more than others.